A Source-Environment-Response (SER) approach for solving Spatio-Temporal Radon Transport in Different Media - Muhammad, Ahmad; Muhammad, Ibrahim Yahaya; Ali, Ahmet H.; Isah, Muhammad Abubakar; Danbatta, Salim Jibrin; Sait, Ahmet Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
In this paper, we introduce a novel method for solving radon transport equation in various media. We derived a general solution, that can be expressed as a normalized superposition of source-term and environmental effects (Constraints). We refer to this approach as Source-Environment-Response (SER) method. We examine the families of solutions generated by the method and demonstrate its applicability to key geological scenarios, including Lithosphere-Atmosphere coupling, radon transport in water, and the simulation of trapped radon during seismic or faulting events. In all cases, the SER method shows strong agreement with established literature. Notably, the method is well suited for inverse modeling problems and can be extended to hybrid formulations for estimating source strength. The Versality and robustness of the SER method make it a valuable tool for modeling radon dynamics in diverse environmental and geophysical contexts.
Keywords: Radon transport; Lithosphere-atmosphere; Source term; Environmental environments; Normalization; SOIL; Geochemistry & Geophysics; Meteorology & Atmospheric Sciences